Turner Syndrome Increases the Risk of Psoriasis: A Systematic Review and Meta-Analysis - Jirat Chenbhanich; Ben Ponvilawan; Patompong Ungprasert (Immuno)
Aims: Patients with Turner syndrome (TS) may have a higher risk of psoriasis as suggested by some reports. Data on this association are still limited. We investigated the association between TS and the risk of prevalent and incident psoriasis by combining results from available studies using systematic reviews and meta-analysis techniques. Methods: Potentially eligible studies were identified from Medline and EMBASE databases from inception to December 2023 using a search strategy that comprised of terms for “Turner syndrome” and “psoriasis”. An eligible cohort study must comprise of two groups of participants—those with and without TS. It must report our outcome of interest—incidence and/or prevalence of psoriasis in each group. The pooled effect estimates were generated using the generic inverse variance method, which assigns weight to each study in reversal to its variance. Meta-analyses of the prevalent and incident psoriasis were conducted separately. Results: A total of 4919 articles were retrieved. After two rounds of independent review by two investigators, five cohort studies (two incident studies and three prevalent studies) met the eligibility criteria and were included in the meta-analyses. The meta-analyses found a significantly elevated risk of both incident and prevalent psoriasis in patients with TS compared to individuals without TS, with the pooled risk ratio of 5.58 (95% CI, 3.73–8.35; I2 0%) and 5.66 (95% CI, 1.52–21.03; I2 19%), respectively. Conclusions: An increased risk of both incident and prevalent psoriasis among patients with TS was demonstrated in this study.